Development and Comparison of Authority of GMS in Limited Companies Based on Statutory Regulations - Prasasti Dyah Nugraheni; Muhammad Reza Wahyu Artura Putra; Moh. Mustakim Fauzan; Muhammad Fatah Agung Nur Tirta Usada (Lambung Mangkurat Law Journal, 2025)
The General Meeting of Shareholders (GMS) serves as the primary decision-making mechanism within a company, carrying legal implications for shareholders and the corporation. However, in practice, different interpretations of the GMS’s authority and its legal impact on shareholders remain complex issues. This study aims to analyze the legal aspects of GMS implementation and its position within corporate decision-making structures. This research employs a normative juridical method with a statutory approach, primarily referring to Law Number 40 of the Year 2007 Concerning Limited Liability Companies as the main legal foundation. The findings indicate that although the GMS is recognized as the highest forum for corporate decision-making, various challenges arise in practice, including legal ambiguities on the extent of GMS authority, conflicts of interest among shareholders, and the enforcement of GMS resolutions that may conflict with Good Corporate Governance principles. Furthermore, this study highlights that legal protection for minority shareholders in GMS decisions requires further reinforcement, particularly in terms of more effective dispute resolution mechanisms. Therefore, clearer policies are needed to balance the interests of majority and minority shareholders while enhancing legal certainty in GMS implementation. The legal finding in this scientific article is that both majority and minority shareholders must have equal fiduciary duties so that if a majority or minority shareholder causes a loss to a company, they can sue the majority or minority shareholder with a derivative lawsuit.